Efficacy of the adjuvanted subunit protein COVID-19 vaccine, SCB-2019: a phase 2 and 3 multicentre, double-blind, randomised, placebo-controlled trial. Issue 10323 (29th January 2022) - Bravo, Lulu; Smolenov, Igor; Han, Htay Htay; Li, Ping; Hosain, Romana; Rockhold, Frank; Clemens, Sue Ann Costa; Roa, Camilo; Borja-Tabora, Charissa; Quinsaat, Antoinette; Lopez, Pio; López-Medina, Eduardo; et al.
Summary: Background: A range of safe and effective vaccines against SARS CoV 2 are needed to address the COVID 19 pandemic. We aimed to assess the safety and efficacy of the COVID-19 vaccine SCB-2019. Methods: This ongoing phase 2 and 3 double-blind, placebo-controlled trial was done in adults aged 18 years and older who were in good health or with a stable chronic health condition, at 31 sites in five countries (Belgium, Brazil, Colombia, Philippines, and South Africa). The participants were randomly assigned 1:1 using a centralised internet randomisation system to receive two 0·5 mL intramuscular doses of SCB-2019 (30 μg, adjuvanted with 1·50 mg CpG-1018 and 0·75 mg alum) or placebo (0·9% sodium chloride for injection supplied in 10 mL ampoules) 21 days apart. All study staff and participants were masked, but vaccine administrators were not. Primary endpoints were vaccine efficacy, measured by RT-PCR-confirmed COVID-19 of any severity with onset from 14 days after the second dose in baseline SARS-CoV-2 seronegative participants (the per-protocol population), and the safety and solicited local and systemic adverse events in the phase 2 subset. This study is registered on EudraCT (2020–004272–17) and ClinicalTrials.gov (NCT04672395 ). Findings: 30 174 participants were enrolled from March 24, 2021, until the cutoff date of Aug 10, 2021, of whom 30 128 received their first assigned vaccine (n=15 064) or a placebo injection (n=15 064). The per-protocol population consisted of 12 355 baseline SARS-CoV-2-naive participants (6251 vaccinees and 6104 placebo recipients). Most exclusions (13 389 [44·4%]) were because of seropositivity at baseline. There were 207 confirmed per-protocol cases of COVID-19 at 14 days after the second dose, 52 vaccinees versus 155 placebo recipients, and an overall vaccine efficacy against any severity COVID-19 of 67·2% (95·72% CI 54·3–76·8), 83·7% (97·86% CI 55·9–95·4) against moderate-to-severe COVID-19, and 100% (97·86% CI 25·3–100·0) against severe COVID-19. All COVID-19 cases were due to virus variants; vaccine efficacy against any severity COVID-19 due to the three predominant variants was 78·7% (95% CI 57·3–90·4) for delta, 91·8% (44·9–99·8) for gamma, and 58·6% (13·3–81·5) for mu. No safety issues emerged in the follow-up period for the efficacy analysis (median of 82 days [IQR 63–103]). The vaccine elicited higher rates of mainly mild-to-moderate injection site pain than the placebo after the first (35·7% [287 of 803] vs 10·3% [81 of 786]) and second (26·9% [189 of 702] vs 7·4% [52 of 699]) doses, but the rates of other solicited local and systemic adverse events were similar between the groups. Interpretation: Two doses of SCB-2019 vaccine plus CpG and alum provides notable protection against the entire severity spectrum of COVID-19 caused by circulating SAR-CoV-2 viruses, including the predominating delta variant. Funding: Clover Biopharmaceuticals and the Coalition for Epidemic Preparedness Innovations.